2012
DOI: 10.1021/mp300379q
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Organic Anion Transporting Polypeptide (OATP) Expression and Its Functional Contribution to the Uptake of Substrates in Human Hepatocytes

Abstract: Since the substrate specificities of OATP1B1, 1B3, and 2B1 are broad and overlapping, the contribution of each isoform to the overall hepatic uptake is of concern when assessing transporter-mediated drug–drug interactions (DDIs) or genetic polymorphism impact in the clinic. Herein, we quantitatively measured OATP proteins in cryopreserved hepatocytes, sandwich-cultured human hepatocytes (SCHH), and the liver, and examined the relationship with functional uptake of OATP substrates in an effort to identify the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
101
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 35 publications
10
101
0
Order By: Relevance
“…Our measured transporter abundances were comparable to previously reported hepatic expression data, albeit we found higher levels of OATP1B1 (Kimoto et al, 2012;Ohtsuki et al, 2012;Bi et al, 2013;Prasad et al, 2014). We speculate that this could be a result of the sample preparation used in our study (Wisniewski et al, 2009), including the membrane fractionation, solubilization, and tryptic digestion.…”
Section: Discussionsupporting
confidence: 89%
“…Our measured transporter abundances were comparable to previously reported hepatic expression data, albeit we found higher levels of OATP1B1 (Kimoto et al, 2012;Ohtsuki et al, 2012;Bi et al, 2013;Prasad et al, 2014). We speculate that this could be a result of the sample preparation used in our study (Wisniewski et al, 2009), including the membrane fractionation, solubilization, and tryptic digestion.…”
Section: Discussionsupporting
confidence: 89%
“…Although there is no clear guidance on the uptake rate required, the initial screen and selection of the hepatocyte lot is critical for success. The expression level of OATP1B1 and OATP1B3 (18.3 and 1.7 fmol/million cells) in the hepatocyte lot used in the study is within the range of the literature reported level (3.4–23.2 for OATP1B1 and 1.5–6.5 for OATP1B3) 27, 28, 29, 30. Because pravastatin undergoes only minimal metabolism and the incubation time was short, metabolism in hepatocyte is likely not an issue in this study.…”
Section: Discussionsupporting
confidence: 80%
“…However, the expression of MRP2 and BCRP was significantly different (1.54 6 0.64 vs. 0.56 6 0.21 and 0.14 6 0.04 vs. 0.70 6 0.22 fmol/mg membrane protein, respectively; P , 0.0001) (Deo et al, 2012;Prasad et al, 2013). Collectively, our transporter data are comparable or modestly lower than those reported previously in a much smaller sample size Bi et al, 2012;Karlgren et al, 2012;Kimoto et al, 2012;Ohtsuki et al, 2012;Tucker et al, 2012). Based on Western blotting, interindividual variability in OATP1B1, OATP1B3, OATP2B1, and P-gp expression have been reported to be 19, 85, 17 (n = 117), and 20-fold (n = 110), respectively (Meier et al, 2006;Nies et al, 2013).…”
Section: Discussionsupporting
confidence: 61%
“…We (Deo et al, 2012;Prasad et al, 2013) and others Bi et al, 2012;Kimoto et al, 2012;Ohtsuki et al, 2012;Schaefer et al, 2012;Tucker et al, 2012) have reported data on the expression of some of these hepatic transporters. Here we extended these studies to determine 1) the interindividual variability in expression of OATP1B1 (SLCO1B1), OATP1B3 (SLCO1B3), OATP2B1 (SLCO2B1), and P-gp (ABCB1) in a large set (n = 64) of human liver samples; and 2) the influence of genotype, age, and sex on such expression.…”
Section: Introductionmentioning
confidence: 93%